The Ciji-Hua’ai-Baosheng II Formula Attenuates Chemotherapy-Induced Anorexia in Mice With H22 Hepatocellular Carcinoma - Xi, Shengyan; Zhai, Xiangyang; Wang, Yanan; Gong, Yuewen; Fu, Biqian; Gao, Chunling; Guo, Xuehui; Li, Yunhong; Wang, Zheng; Huang, Shuqiong; Lu, Dawei; Zhao, Yufang; et al. (Frontiers in Pharmacology, 2021)
Background: Ciji-Hua’ai-Baosheng II Formula (CHB-II-F) is a traditional Chinese medicine formula, which specifically targets different aspects of chemotherapy-induced adverse effects in patients with cancer. In our clinical application, CHB-II-F significantly alleviated chemotherapy-induced anorexia (loss of appetite) and improved the quality of life for patients with tumor during and after chemotherapy. However, the mechanism of CHB-II-F in alleviation of chemotherapy-induced anorexia remains to be further investigated. Aim of Study: To explore the therapeutic effect and mechanism of CHB-II-F on chemotherapy-induced anorexia in the mice model of H22 hepatoma. Materials and Methods: A total of 72 Kunming mice of SPF grade were inoculated subcutaneously with H22 hepatoma cells into the right anterior armpit of the mice. After 1 week of seeding, mice were injected intraperitoneally with a high dose of 5-fluorouracil (200 mg/kg 5-FU) to establish the model of chemotherapy. The mice were randomly divided into six groups: untreated group, 5-FU group, 5-FU plus Yangzheng Xiaoji capsule (YZXJC) group, and three groups of 5-FU plus different concentrations of CHB-II-F. All the mice in each group were treated for 14 days. The body weight, food intake, tumor volume, and tumor weight of mice were measured, and pathological examinations of tumor tissue, stomach, and duodenum were carried out. Expressions of serum Leptin, Neuropeptide Y (NPY), epidermal cell growth factor (EGF), Motilin (MTL), Orexin A (OXA), Gastrin (GAS), Ghrelin, Prostaglandin E2 (PGE2), and jejunum superoxide dismutase (SOD) activity and malondialdehyde (MDA) content were examined. The protein and mRNA levels of proopiomelanocortin (POMC), Orexin receptor 1 (OX1R), neuropeptide Y (NPY), cocaine and amphetamine regulated transcript peptide (CART), Agouti gene-related protein (AgRP), Leptin receptor (Ob-R), and Ghrelin receptor (GHSR) were examined in hypothalamus, and the protein levels of substance P (SP) and 5-hydroxytryptamine (5-HT) in duodenum were measured. Results: The combination of CHB-II-F and 5-FU could enhance the inhibitory effect of 5-FU on tumor. The tumor inhibition rates of 5-FU group, YZXJC group, CHB-II-F(H) group, CHB-II-F(M) group, and CHB-II-F(L) group were 58.88, 28.08, 54.96, 37.69, and 28.61%, respectively. Compared with untreated group and 5-FU group, CHB-II-F significantly increased the body weight and food intake of tumor-bearing mice; increased the content of NPY, Orexin A, Ghrelin, GAS, MTL, EGF, and PGE2 in serum and the activity of SOD in jejunum; and decreased the content of Leptin in serum and the content of MDA in jejunum. Compared with untreated group and 5-FU group, CHB-II-F also enhanced the expression of OX1R, GHSR, NPY, and AgRP protein and gene and decreased the expression of Ob-R, POMC, and CART protein and gene in hypothalamus of mice, and the gene expression was consistent with the protein expression. In addition, CHB-II-F decreased the expression of 5-HT and SP protein in duodenum. Conclusion: In the murine model of H22 hepatocellular carcinoma (HCC) receiving chemotherapy, CHB-II-F enhances the inhibitory effect of 5-FU on tumor, significantly improves the pathological injury of gastrointestinal tract caused by chemotherapy, and regulates the secretion of gastrointestinal hormones. It may alleviate chemotherapy-induced anorexia by affecting appetite regulatory factors in the feeding area of hypothalamus central nervous system and peripheral appetite regulatory factors.